Penerapan Jaminan Mutu Pelayanan Kesehatan di Puskesmas dalam Meningkatkan Mutu Layanan Jaminan Kesehatan - Rini Herdiani (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Community health centers (Puskesmas), as first-level health care facilities, play a strategic role in providing quality health care, particularly in supporting the implementation of health insurance. Implementing quality assurance in health care is a crucial aspect in ensuring safe, effective, efficient, and patient-oriented services. This Community Service activity aims to improve the understanding and implementation of quality assurance in health care centers in order to improve the quality of health care services. Implementation methods include counseling, discussions, mentoring in the implementation of quality standards, and evaluation. The results of the activity indicate an increase in health workers' understanding of the concept of quality assurance and improvements in the implementation of service standards. The implementation of quality assurance is expected to improve service quality, patient satisfaction, and public trust in health care services at Puskesmas.